ANALISIS PENERAPAN KURIKULUM MADRASAH 2019: KAJIAN BUKU TEKS BINA FIQIH KELAS V SD/MI - Amarullah, Muhamad; Firdaus, Iqlima; Jannah, Mifthaul; Salamah, Huri; Nopasari, Dewi (Sindoro: Cendikia Pendidikan, 2025)
Textbooks have an important role in the learning process both for students as a source of learning materials and for teachers as teaching guidelines. This study aims to evaluate the textbook "Bina Fiqih" for class V Madrasah Ibtidaiyah (MI) based on aspects of content, presentation, language, and graphics. The method used in this study is the literature study method. Literature study is a series of activities related to collecting library data, reading, recording and processing research materials in the form of books, journal articles, and curriculum documents. The results of the study show that this book is very worthy of use as a teaching material with an overall score of 89.1%, which is included in the category of "very feasible". The advantages of books include the suitability of the material with the curriculum, simple language, and systematic presentation structure. However, there are several shortcomings, such as the lack of attractive illustrations and the lack of technology in learning. These findings provide recommendations for further development to increase the effectiveness of books as a learning medium. Keywords: Textbooks, Fiqh Development, Madrasah Curriculum 2019